(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to develop and check the causal relationship model of audit quality of cooperatives auditors in Thailand with empirical data. The researchers defined the population as cooperative auditors in Thailand and cooperatives in the responsibility totaling 2,598 peoples while the sample as totaling 920 peoples. Data was collected by questionnaires for opinions about the cooperative audit quality. Data was analysis through by structural equation model (SEM). The research result showed that 1) the factors that affected audit quality were professional ethics, professional skepticism and audit process. The audit quality indicators were accurate and timely report, reliable cooperative financial statements, notices and faults timely and suggestions which beneficial to cooperative management and 2) the causal model of audit quality of cooperative auditors in Thailand was consistent with the empirical data. The cooperative auditors should be developed and encouraged to have knowledge and understanding in professional ethics, professional skepticism and audit process in order to improve the quality of cooperative auditing as appropriate for the expectations of the society from cooperative auditors.